Sustainable synthesis of cucumber-derived gold and silver nanoparticles: impact on mungbean root-rot disease suppression, and organic LED performance - Shahid, Shumaila; Kumar, Arvind; Khan, Mohd Shoeb; Ansari, Nizamul Haque; Kareem, Abdul; Nagar, Mangey Ram; Rizvi, Navaid Zafar; Rahman, Safikur; Ahmad, Shabbir; Kaushik, Parshant (Frontiers in Nanotechnology, 2025)
This is the first study that reports in vivo antifungal efficacy of cucumber-derived green synthesized silver and gold nanoparticles (Ag and Au NPs) against root-rot disease of mungbean caused by Macrophomina phaseolina. Numerous spectral and morphological studies including UV–Vis, FT-IR, TGA, DLS, TEM, SEM, and EDX were performed that determine the successful preparation of Ag/Au NPs and confirmed their particle size and crystalline structure. The biosynthesized NPs were first tested under in vitro condition which showed 55%–74% mycelial inhibition of M. phaseolina. In vivo experiment clearly demonstrated that both the nanoparticles significantly controlled root-rot disease of mungbean. Maximum control of disease (47%) was found with Ag NPs at 100 ppm with significant improvement in the plant growth (38%–45%) and yield (59%). Au NPs (100 ppm) also gave a satisfactory control of root-rot disease (42%) and increased grain yield of infected plants by 49%. As the results of TGA revealed that Ag NPs were thermally more stable than Au NPs, hence, additionally we explored the impact of Ag NPs on thermally-activated delayed fluorescent (TADF) organic LED performance to broaden their application potential. We found that incorporating Ag NPs into hole-injection layer significantly enhances the performance of TADF organic LED. This research not only demonstrates the potential of green-synthesized Ag and Au NPs as effective nanofungicides for mungbean root-rot disease management, but also highlights their promising role in enhancing the performance of advanced electronic devices such as TADF organic LEDs, thus broadening their scope of application in both agriculture and optoelectronics.